Respuesta :

Answer:

[B] - 1/3

Step-by-step explanation:

Given:

-8x-5(1-x)=6x-2

Solve:

Expand : -8x - 5(1-x) : -3x -5

-3x - 5 = 6x -2

Add 5 to both sides (Balance)

-3x-5+5=6x-2+5

Simplify

-3x = 6x + 3

subtract 6x to both sides (Balance)

-3x - 6x = 6x +3 -6x

Simplify

-9x = 3

Divide both sides by -9 (Balance)

-9x/-9=3/-9

Simplify

x = -1/3

[RevyBreeze]

ANSWER: The value of x that makes the given equation true is: B. -1/3

EXPLANATION:

1} First, we need to simplify both sides of the equation.

−8x−5(1−x)=6x−2

−8x+(−5)(1)+(−5)(−x)=6x+−2 [Note: We need to Distribute]

−8x+−5+5x=6x+−2

(−8x+5x)+(−5)=6x−2 [Note: We need to Combine Like Terms]

−3x+−5=6x−2

−3x−5=6x−2

2} Then, we need to subtract 6x from both sides.

−3x−5−6x=6x−2−6x

−9x−5=−2

3} Next, we need to add 5 to both sides.

−9x−5+5=−2+5

−9x=3

4} Finally, we need to divide both sides by -9.

-9x/-9 = 3/-9

x = -1/3

Therefore, the answer is B. -1/3